Handbook of Signal Processing Systems - Bhattacharyya, Shuvra S.; Deprettere, Ed F.; Leupers, Rainer; Takala, Jarmo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In this new edition of the Handbook of Signal Processing Systems, many of the chapters from the previous editions have been updated, and several new chapters have been added. The new contributions include chapters on signal processing methods for light field displays, throughput analysis of dataflow graphs, modeling for reconfigurable signal processing systems, fast Fourier transform architectures, deep neural networks, programmable architectures for histogram of oriented gradients processing, high dynamic range video coding, system-on-chip architectures for data analytics, analysis of finite word-length effects in fixed-point systems, and models of architecture. There are more than 700 tables and illustrations; in this edition over 300 are in color. This new edition of the handbook is organized in three parts. Part I motivates representative applications that drive and apply state-of-the art methods for design and implementation of signal processing systems; Part II discusses architectures for implementing these applications; and Part III focuses on compilers, as well as models of computation and their associated design tools and methodologies. .
1 Signal Processing Methods for Light Field Displays. 2 Inertial Sensors and Their Applications -- 3 Finding It Now: Construction and Configuration of Networked Classifiers in Real-Time Stream Mining Systems -- 4 Deep Neural Networks: A Signal Processing Perspective -- 5 High Dynamic Range Video Cooling -- 6 Signal Processing for Control -- 7 MPEG Reconfigurable Video Coding -- 8 Signal Processing for Wireless Transceivers -- 9 Signal Processing for Radio Astronomy -- 10 Distributed Smart Cameras and Distributed Computer Vision -- 11 Arithmetic -- 12 Coarse Grained Reconfigurable Array Architectures -- 13 High Performance Stream Processing on FPGA -- 14 Application-specific Accelerators for Communications -- 15 System-on-chip Architectures for Data Analytics -- 16 Architectures for Stereo Vision -- 17 Hardware Architectures for the Fast Fourier Transform -- 18 Programmable Architectures for Histogram of Oriented Gradients Processing -- 19 Methods and Tools for Mapping Process Networks onto Multi-Processor Systems-on-chip -- 20 Intermediate Representations for Simulation and Implementation -- 21 Throughput Analysis of Dataflow Graphs -- 22 Dataflow Modeling for Reconfigurable Signal Processing Systems -- 23 Integrated Modeling Using Finite State Machines and Dataflow Graphs -- 24 Kahn Process Networks and a Reactive Extension -- 25 Decidable Signal Processing Dataflow Graphs -- 26 Systolic Arrays -- 27 Compiling for VLIW DSPs -- 28 Software Compilation Techniques for Heterogeneous Embedded Multi-Core Systems -- 29 Analysis of Finite Word-Length Effects in Fixed-Point Systems -- 30 Models of Architecture for DSP Systems -- 31 Optimization of Number Representations -- 32 Dynamic Dataflow Graphs.
Keywords: Signal processing; Telecommunication; Microprocessors; Computer architecture; Signal, Speech and Image Processing .; Communications Engineering, Networks; Processor Architectures